Assessing Pain among Chinese Elderly-Chinese Health and Retirement Longitudinal Study - Tong YU; Jun MA; Yan JIANG; Jian LI; Yunlong Gen; Yufeng WEN; Wenjie SUN (Tehran University of Medical Sciences, 2018)
Background: Body pain is an important issue among elderly. The objective of this study was to access the association between the socioeconomic status and pain among elderly Chinese. Methods: This nationally representative sample cohort study, China Health and Retirement Longitudinal Study (CHARLS), was conducted to estimate pain prevalence and risk factors from Jun 2011 to Mar 2012. Body pain was evaluated by the questionnaires. Logistic regression model was applied to estimate the odds ratio (OR) and 95% Confidence Interval (95% CI) of body pain to identify the potential risk factors. Results: The prevalence of pain was increased with age (P<0.05). For moderate pain vs. no pain, doing agriculture job (OR 1.17; 95 CI 1.05-1.31), living in urban (OR 0.80; 95 CI 0.72-0.90), having a health problem (OR 1.55; 95 CI 1.20-1.99) is associated with moderate pain. For severe pain vs. no pain, primary school education (OR 0.65; 95 CI 0.54-0.78), junior high school education (OR 0.48; 95 CI 0.39-0.59), having a physical disability (OR 2.71; 95 CI 2.18-3.37), never drinker (OR 0.74; 95 CI 0.60-0.91), environment of urban (OR 0.54; 95 CI 0.46-0.63), having a health problem (OR 2.03; 95 CI 1.45-2.83) are associated with severe pain. Conclusion: Socioeconomic variables such as education, occupation and health conditions are associated with both moderate severe pains.